Aesthetics and anthropology cogitations - Elhaik, Tarek (Routledge, an imprint of the Taylor & Francis Group, 2022)
"This book focuses on the reconfiguration of aesthetic anthropology into an anthropological problem of cogitation, opening up a fascinating new dialogue between the domains of anthropology, philosophy, and art. Tarek Elhaik embarks on an inquiry composed of a series of cogitations based on fieldwork in an ecology of artistic and scientific practices: from conceptual art exhibitions to architectural environments; from photographic montages to the videotaping of spirit seances; from artistic interventions in natural history museums to ongoing dialogues between performance artists and marine scientists. The chapters examine the image-work, ethical demands, and aesthetic struggles of interlocuters including artists Mathias Goeritz, Mounir Fatmi, Silvia Gruner, Joan Jonas, and Patricia Lagarde."--Provided by publisher.